Nickel-Catalyzed Suzuki–Miyaura Cross-Coupling in a Green Alcohol Solvent for an Undergraduate Organic Chemistry Laboratory - Hie, Liana (J Chem Educ, 2014)
[Image: see text] A modern undergraduate organic chemistry laboratory experiment involving the Suzuki–Miyaura coupling is reported. Although Suzuki–Miyaura couplings typically employ palladium catalysts in environmentally harmful solvents, this experiment features the use of inexpensive nickel catalysis, in addition to a “green” alcohol solvent. The experiment employs heterocyclic substrates, which are important pharmaceutical building blocks. Thus, this laboratory procedure exposes students to a variety of contemporary topics in organic chemistry, including transition metal-catalyzed cross-couplings, green chemistry, and the importance of heterocycles in drug discovery, none of which are well represented in typical undergraduate organic chemistry curricula. The experimental protocol uses commercially available reagents and is useful in both organic and inorganic instructional laboratories.